The Effect of Technology Integration, Work-Life Balance, and Job Stress on Employee Well-Being in the Art Industry in Jakarta - Nanny Mayasari; Ade Suhara; Sri Dinarwati; Hilda Yuliastuti; Reynaldi Tresnadjaja (Westscience Press, 2024)
This quantitative study investigates the impact of technology integration, work-life balance, and job stress on employee well-being within the art industry in Jakarta. Through a cross-sectional survey of 150 professionals, data were collected and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The measurement model assessment confirmed the reliability and validity of the measurement instrument, while the structural model estimation revealed significant direct and indirect effects among the variables. The findings indicate that technology integration positively influences employee well-being, while work-life balance and job stress play significant roles in shaping employee welfare. These results underscore the importance of organizational strategies and interventions aimed at promoting a healthier, more supportive work environment within the art industry. The study contributes to a deeper understanding of the factors influencing employee well-being in the context of creative professions and provides valuable insights for organizational leaders, policymakers, and practitioners.